MEMPERTIMBANGKAN KERAWANAN LONGSOR DALAM ARAHAN PENGGUNAAN LAHAN BERHUTAN DI KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - Djuariah, Rina; Senawi; Setyarso, Agus; Machfud, Maksum M. (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2016)
Forest transition in rural area derived by community landowner and supported by Indonesian Government Reforestation Programme at beginning. Meanwhile, landslide still occur in some region as well as Kulon Progo District of Yogyakarta Province. Land evaluation is needed in order to review forest land-use parcel due to landslide susceptibility. This research combines some procedures consists of Land Capability Analysis by scoring method regarding to Land Capability Assessment published by USDA (United States Departement of Agriculture) followed by Land Suitability Analysis, and forestland use planning by scoring method regarding to Ministry of Agriculture Declare number 837/Kpts/UM/11/1980 and number 683/Kpts/UM/8/1981 followed by Suitability Analysis. The results showing the wide range of land capability classes, i.e. I, II, III, IV, VI and VII. Result of Land Suitability Analysis showing generally Suitable Land-use, but Not Suitable for settlement in VI and VII classes of Land Capability also for Paddy Field in IV, VI and VII classes. The study area can be classified as protected zone 5,06%, buffer zone 41,16%, and cultivated zone 24,61%, when 65,40%, 29,40% and 3,69% for Suitable used, Positively Not Suitable and Negatively Not Suitable respectively. High pressure land use founded in steep land of mountainous area by respiratory cliff for settlement and road among high density of tree crown. Proposed land use for forestland by these procedures still inadequate due to the map scale used for rural area wiches unseparate land use for woodland and peasant's house. Future research need into account for landslide susceptibility assessment in specific site used for settlement among the forest cover due to the sustainable land-use and safety life. Keywords : Forest Transition, Land Capability, Landslide Vulnerability, Land Directives, Forestland Use